Implementasi Manajemen Berbasis Sekolah Dalam Mewujudkan Sekolah Islam Unggulan - Muhammad Nur Hakim (Nidhomul Haq : Jurnal Manajemen Pendidikan Islam, 2016)
School-based management is implemented so that it can give ease in achieving the vision, mission, and goals of the institution, so that it can improve the quality of education and bring a good end result and quality, and can get a productive and qualified graduates. This research was conducted in SMP Ar-Rohmah and SMP Plus Al-Kauthar Malang, where the school is the educational institution that has a future orientation. The institutions including educational institutions featured with learners who are full of achievement in terms of both academic and non-academic. This study focused on four issues, are: 1) The factors that encourage the implementation of MBS; 2) The principles of what is done in the implementation of MBS; 3) What is the purpose of implementation of MBS; and 4) How does the structural components MBS implementation.This study used qualitative methods, multi-sites. data collection used the interview, observation and documentation. The research findings were: 1) the factors that encourage the implementation of MBS is: (a) the existence of decentralization; (b) a factor of independence against a school owned resources; (c) factors initiative; and (d) a factor of innovation against the increase in the quality of education. Then the purpose of the implementation of the MBS, namely: (a) so that the school could improve the quality of education by making the school more independent, have awareness/participation, teamwork, initiative and school in managing, utilizing, and empower the resources available; (b) the school can be more generous in taking decisions together and initiate and innovate in the process of improving the quality of education. 2) Then there are structural components of the MBS implementation, namely: (a) the management of curriculum and instructional programs; (b) the management of produce educators in schools; (c) the student Management; (d) financial management and financing; (e) management of educational facilities and infrastructure; (f) management the management of the school and community relations; (g) the management of special service institution that is effective and efficient.